2004
DOI: 10.1104/pp.104.047548
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Dehydrogenase of Tobacco Is Mainly Induced in the Cytosol of Phloem Companion Cells When Ammonia Is Provided Either Externally or Released during Photorespiration

Abstract: Glutamate (Glu) dehydrogenase (GDH) catalyses the reversible amination of 2-oxoglutarate for the synthesis of Glu using ammonium as a substrate. This enzyme preferentially occurs in the mitochondria of companion cells of a number of plant species grown on nitrate as the sole nitrogen source. For a better understanding of the controversial role of GDH either in ammonium assimilation or in the supply of 2-oxoglutarate (F. Dubois, T. Tercé-Laforgue, M.B. Gonzalez-Moro, M.B. Estavillo, R. Sangwan, A. Gallais, B. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
1
9

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(99 citation statements)
references
References 47 publications
(62 reference statements)
2
84
1
9
Order By: Relevance
“…Moreover, the close location of the CC-SE complexes to a small number of xylem elements appears to be a prerequisite for a direct xylem-phloem transfer of amino acids translocated from roots (Atkins, 2000). The enzymes of ammonium metabolism, including cytosolic GS1 Kamachi et al, 1992;Pereira et al, 1992), Asn synthetase (Nakano et al, 2000), and GDH (Tercé-Laforgue et al, 2004), are colocalized in the companion cells as well. Although there is no molecular evidence showing that amino acid trafficking takes place by broad affinity amino acid transporters in minor veins (Fischer et al, 1998;van Bel, 2003), phloem loading of Gln, Asn, and Glu from CC-SE complexes likely regulates nitrogen translocation in the sieve streams where these amino acids are maintained at the constant levels.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, the close location of the CC-SE complexes to a small number of xylem elements appears to be a prerequisite for a direct xylem-phloem transfer of amino acids translocated from roots (Atkins, 2000). The enzymes of ammonium metabolism, including cytosolic GS1 Kamachi et al, 1992;Pereira et al, 1992), Asn synthetase (Nakano et al, 2000), and GDH (Tercé-Laforgue et al, 2004), are colocalized in the companion cells as well. Although there is no molecular evidence showing that amino acid trafficking takes place by broad affinity amino acid transporters in minor veins (Fischer et al, 1998;van Bel, 2003), phloem loading of Gln, Asn, and Glu from CC-SE complexes likely regulates nitrogen translocation in the sieve streams where these amino acids are maintained at the constant levels.…”
Section: Discussionmentioning
confidence: 96%
“…16,21 GDH catalyzes the reversible amination of 2-oxoglutarate (2OG) for the synthesis of Glu using ammonium as a substrate. 22 Recent reverse-genetic research revealed that the main physiological function of NADH-GDH is to provide 2OG for the tricarboxylic acid cycle. 23 It would make sense to compare the Glu concentrations of a quadruple knock out (nadh-gogat, gdh1-2-3) with that of single knock out mutant (nadhgogat) under high ammonium conditions in order to study the conjunction of NADH-GOGAT with GDH.…”
Section: 3mentioning
confidence: 99%
“…In leaves with elevated NH 4 1 levels (e.g. senescing leaves), GDH protein is also detected in the cytosol of phloem companion cells (Paczek et al, 2002;Dubois et al, 2003;Tercé-Laforgue et al, 2004a;Kichey et al, 2005;Fontaine et al, 2006).…”
mentioning
confidence: 99%